SPECIAL VALUES OF SHIFTED CONVOLUTION DIRICHLET SERIES. Issue 1 (16th June 2015) - Mertens, Michael H.; Ono, Ken
Abstract : In a recent important paper, Hoffstein and Hulse [Multiple Dirichlet series and shifted convolutions, arXiv:1110.4868v2 ] generalized the notion of Rankin–Selberg convolution L ‐functions by defining shifted convolution L ‐functions. We investigate symmetrized versions of their functions, and we prove that the generating functions of certain special values are linear combinations of weakly holomorphic quasimodular forms and "mixed mock modular" forms.